Molecular landscape of sex- and modality-specific exercise adaptation in human skeletal muscle through large-scale multi-omics integration - Macsue Jacques; Shanie Landen; Adam P. Sharples; Andrew Garnham; Ralf Schittenhelm; Joel Steele; Aino Heikkinen; Elina Sillanpää; Miina Ollikainen; James Broatch; Navabeh Zarekookandeh; Ola Hanson; et al. (Cell Reports)
Summary: We investigated the molecular mechanisms of exercise adaptations in human muscle by integrating genome, methylome, transcriptome, and proteome data from over 1,000 participants (2,340 muscle samples). We identified distinctive signatures associated with maximal oxygen consumption (VO2max), and multi-omics integration uncovered five key genes as robust exercise markers across layers, with transcription factors functioning as activators, synergizing with DNA methylation to regulate gene expression. Minimal sex differences were observed, while modality-specific analysis highlighted distinct pathways for aerobic and resistance exercise, contrasting with muscle disuse patterns. Finally, we created a webtool, OMAx, featuring our individual omics and integration analysis. These findings provide a comprehensive multi-omics framework for understanding exercise-induced molecular adaptations, offering insights into muscle health, cardiorespiratory fitness, and their roles in aging and disease prevention.